1998
DOI: 10.1523/jneurosci.18-24-10553.1998
|View full text |Cite
|
Sign up to set email alerts
|

D1Receptor in Interneurons of Macaque Prefrontal Cortex: Distribution and Subcellular Localization

Abstract: Working memory performance is influenced by dopamine activation of D1 family dopamine receptors in the prefrontal cortex; working memory performance is maximal at moderate stimulation of D1 family receptors and is reduced by either higher or lower levels of D1 stimulation. The neuronal mechanisms that underlie this complex relationship are not yet understood. Previous work from this laboratory has demonstrated that the D1 family receptors, D1and D5, are located in different compartments of pyramidal cells. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
131
1
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 205 publications
(148 citation statements)
references
References 67 publications
15
131
1
1
Order By: Relevance
“…The SSCs were almost exclusively localized in the perisomatic region of pyramidal cells, whereas they occurred rarely in perikarya and were virtually absent from the proximal processes of interneurons (see Materials and Methods for identification criteria). These rarely occurring SSCs in nonpyramidal neurons were never seen in association with DARs [see Khan et al (2001) for D 2 R, Muly et al (1998) for D 1 R]. In addition, both the D 5 R protein and D 5 R mRNA are localized predominantly in pyramidal neurons (Bergson et al, 1995a;Ariano et al, 1997;Ciliax et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…The SSCs were almost exclusively localized in the perisomatic region of pyramidal cells, whereas they occurred rarely in perikarya and were virtually absent from the proximal processes of interneurons (see Materials and Methods for identification criteria). These rarely occurring SSCs in nonpyramidal neurons were never seen in association with DARs [see Khan et al (2001) for D 2 R, Muly et al (1998) for D 1 R]. In addition, both the D 5 R protein and D 5 R mRNA are localized predominantly in pyramidal neurons (Bergson et al, 1995a;Ariano et al, 1997;Ciliax et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Potential mechanisms have been attributed to the different receptor subtypes, their differential affinities to agonist and their differential cellular or subcellular distributions [1,5,6,[31][32][33][34] .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the use of dopamine or a nonspecific agonist in these experiments would activate both types of receptors, perhaps resulting in the physiological effects from activation of one receptor type canceling out those caused by agonism of the other (Trantham-Davidson et al, 2004). Parvalbumin-containing fast-spiking interneurons are particularly sensitive to D 1 -like receptor activation compared with calbindin-expressing, low-thresholdspiking cells, reflecting the preferential expression of this receptor in the former (Le Moine and Gaspar, 1998;Muly et al, 1998;Gorelova et al, 2002;Paspalas and Goldman-Rakic, 2005;Kroner et al, 2007). The proportion of PV-immunoreactive neurons that express the D 1 receptor is particularly high (Ͼ60%) in the infragranular layers.…”
Section: -Like Receptor Activation Alters the Intrinsic Propertiementioning
confidence: 99%
“…We found that application of a D 1 -like agonist reduced IPSCs by approximately one-third. D 1 receptors are present on both presynaptic and postsynaptic compartments of FS cells (Muly et al, 1998;Paspalas and Goldman-Rakic, 2005), so it is conceivable that the D 1 -like receptor-mediated depression of IPSCs could have a presynaptic site of action, a postsynaptic mechanism, or a combination of both. Our finding that SKF81297 increased the coefficient of variation of IPSC amplitudes suggests that activation of presynaptic D 1 -like receptors affected the release of GABA and reduced the amplitude of GABAergic postsynaptic events.…”
Section: Depression Of Gabaergic Inhibition Between Fs Cellsmentioning
confidence: 99%